Pengabdian Kepada Masyarakat Pengembangan Produk Olahan Hasil Tangkap Perikanan dengan Memperdayakan Kelompok Wanita Pesisir Desa Pegagan Kecamatan Pademawu Kabupaten Pamekasan Provinsi Jawa Timur - Mohammad Taufiq Hidayat (Yayasan Literasi Sains Indonesia, 2022)
Market demand for the availability of fishery products is relatively high, so processed fishery products business can be the right choice to start a business in order to improve the economy of a creative community. This also happened in Pamekasan Regency. As one of the regencies in Madura which is famous for its education city, Pamekasan Regency is also known as a culinary city. The need for supplies of culinary ingredients such as fish, crabs and shellfish is still very high. To fulfill it, efforts to increase production are needed. The partners of this program are fishermen women's groups in Pegagan Village, Pademawu District. Partners have a strong desire for entrepreneurship, especially in fulfilling the supply of fish or fishery products for culinary businesses in Pamekasan Regency and its surroundings. However, limited fishery products are a separate problem faced by partners in processing fishery products to meet the needs of existing culinary businesses. Limitations in the processing of fishery products require careful thought in an effort to empower something that is productive to become a creative economy. One of the right choices so that they can still manage fishery products is to provide assistance and outreach by presenting material on how to properly and properly process fishery products. This program is carried out using training and mentoring methods. The training includes product manufacturing training and product marketing management cultivation training while mentoring is carried out through training, marketing and financial analysis. In the mentoring phase, monitoring and evaluation will also be carried out to ensure the sustainability of the program. The output of this program is the increased production of fishery products from Pegagan Village fisherman groups. Other outputs from this program are publications in Proceedings and national scientific journals with ISSN, e-ISSN and publications in the mass media.